A phenomenological elevated temperature friction model for viscoelastic polymer coatings based on nanoindentation. (March 2018) - Lan, Pixiang; Zhang, Youfeng; Dai, Wei; Polycarpou, Andreas A.
Abstract: We propose a phenomenological elevated temperature (up to 260 °C) friction model for viscoelastic polymer coatings based on high temperature nanoindentation. Two advanced polymeric coatings were selected for this study, namely Aromatic Thermosetting Polyester (ATSP) and Polyetheretherketone (PEEK). High temperature up to 260 °C nanoindentation experiments were conducted at the same temperatures as macro-scale ball-on-disk tribological experiments at different temperatures. Hardness was directly measured from the indentation experiments and viscosity/relaxation and elastic modulus were obtained by curve fitting of the nanoindentation's unloading curve using a quadratic Maxwell model. The two coatings showed decreasing hardness, elastic modulus and viscosity/relaxation trends, with increasing temperature. The ATSP coating exhibited higher indentation recovery rate and higher hardness, and thus better wear resistance. Highlights: Phenomenological friction model for polymeric coatings. High temperature nanoindentation experiments to obtain elastic & viscous properties. ATSP coating has higher hardness and better wear resistance than PEEK coating.